Sumoylation and transcription regulation at nuclear pores - Texari, Lorane (Chromosoma, 2014)
Increasing evidence indicates that besides promoters, enhancers, and epigenetic modifications, nuclear organization is another parameter contributing to optimal control of gene expression. Although differences between species exist, the influence of gene positioning on expression seems to be a conserved feature from yeast to Drosophila and mammals. The nuclear periphery is one of the nuclear compartments implicated in gene regulation. It consists of the nuclear envelope (NE) and the nuclear pore complexes (NPC), which have distinct roles in the control of gene expression. The NPC has recently been shown to tether proteins involved in the sumoylation pathway. Here, we will focus on the importance of gene positioning and NPC-linked sumoylation/desumoylation in transcription regulation. We will mainly discuss observations made in the yeast Saccharomyces cerevisiae model system and highlight potential parallels in metazoan species.